The persistence of biofilm-associated antibiotic resistance of Staphylococcus aureus isolated from clinical bovine mastitis cases in Australia - Babra, C.; Gogoi Tiwari, Jully; Pier, G.; Thein, T.H.; Sunagar, R.; Sundareshan, S.; Isloor, S.; Hegde, N.; De Wet, S.; Deighton, M.; Gibson, J.; Costantino, Paul; et al. (Springer, 2013)
The aim of this investigation was to determine the persistence of biofilm-associated antibiotic resistance developed by methicillin-sensitive Staphylococcus aureus (MSSA), of different capsular types, during biofilm formation. Becauseof superiority of the tissue culture plate (TCP) over the CongoRed Agar (CRA) method for measuring biofilm formation, it was used to determine the persistence of the antibiotic resistance developed by the isolates in biofilms. The antibiotic resistance was found to persist for 3–4 wk post-propagation as planktonic subcultures. Interestingly, some strains even developed resistance to vancomycin and/or teicoplanin. However, no association of either biofilm formation or persistent antibiotic resistance with the major capsular phenotype was observed.These observations highlight the potential significance of (a) determining the antibiograms of S. aureus subcultured from biofilms developed in vitro using the TCP method as well as from planktonic cultures for formulation of an optimal therapeutic strategy, and (b) continuing to identify predominant non-capsular antigens contributing to biofilm formation, regardless of the capsular phenotype for the development of an effective potentially broad-spectrum vaccine for prevention of bovine mastitis caused by S. aureus.